Optimization of extraction and purification of the M protein fused GCN4pII motif and elastin like polypeptide of porcine epidemic diarrhea virus from Nicotiana benthamiana - Tran, Thu Hoai; Chu, Hoang Ha; Ho , Thi Thuong; Pham, Bich Ngoc (Vietnam Journal of Biotechnology, 2024)
Porcine Epidemic Diarrhea (PED) has significantly impacted the swine farming industry in several countries worldwide, including Vietnam. Porcine Epidemic Diarrhea Virus (PEDV) has been proven to be the cause of PED. The COE and M proteins are potential candidates for subunit vaccine research against PEDV. The M protein, a largest envelope protein of PEDV, is highly conserved and plays a crucial role in virus assembly as well as in inducing the production of virus-neutralizing antibodies in the presence of complement. In a previous study, we constructed and expressed the M protein fused with the GCN4pII motif and Elastin-Like Polypeptide (M-pII-ELP) separately from the COE/G2a-pII protein in Nicotiana benthamiana. In this study, we assessed the co-expression of M-pII-ELP and COE/G2a-pII proteins in N. benthamiana using SDS-PAGE and Western blot. Next, we verified the assembly of virus-like particles (VLPs) by the M-pII-ELP protein alone through Transmission Electron Microscopy (TEM) analysis after ultracentrifugation with a sucrose gradient. Suitable buffers for the extraction and purification of M-pII-ELP protein using immobilized affinity chromatography (IMAC) were also selected. Results from SDS-PAGE and Western blot confirmed the co-expression of M-pII-ELP and COE/G2a-pII proteins in the plant; however, the expression of COE/G2a-pII protein was suppressed when co-expressed with M-pII-ELP. TEM analysis confirmed the formation of virus-like particles based on the assembly of the M-pII-ELP protein. Among the buffers tested for M-pII-ELP protein extraction, Tris-HCl buffer yielded the highest amount of M-pII-ELP protein. It was determined that the optimal imidazole concentrations for extraction and washing buffers in M-pII-ELP protein purification are 0 mM and 10 mM, respectively. These results lay the groundwork for further studies on developing plant-based subunit vaccines against PEDV.